Gas migration pathways, controlling mechanisms and changes in sediment acoustic properties observed in a controlled sub-seabed CO2 release experiment. (July 2015) - Cevatoglu, Melis; Bull, Jonathan M.; Vardy, Mark E.; Gernon, Thomas M.; Wright, Ian C.; Long, David
Highlights: Repeated 2D seismic reflection surveys map migration of CO2 in marine sediments. CO2 is imaged as bright spots, acoustic blanking, and by reflector terminations. Seismic chimneys are interpreted as inter-connected micro-scale fractures. CO2 migration is controlled by stratigraphy and total subsurface gas volume/injection rate. CO2 changes sediment acoustic properties, including reflectivity and attenuation. Abstract: Carbon capture and storage (CCS) is a key technology to potentially mitigate global warming by reducing carbon dioxide (CO2 ) emissions from industrial facilities and power generation that escape into the atmosphere. To broaden the usage of geological storage as a viable climate mitigation option, it is vital to understand CO2 behaviour after its injection within a storage reservoir, including its potential migration through overlying sediments, as well as biogeochemical and ecological impacts in the event of leakage. The impacts of a CO2 release were investigated by a controlled release experiment that injected CO2 at a known flux into shallow, under-consolidated marine sediments for 37 days. Repeated high-resolution 2D seismic reflection surveying, both pre-release and syn-release, allows the detection of CO2 -related anomalies, including: seismic chimneys; enhanced reflectors within the subsurface; and bubbles within the water column. In addition, reflection coefficient and seismic attenuation values calculated for each repeat survey, allow the impact of CO2 flux on sediment acoustic properties to be comparatively monitored throughout the gas release. CO2 migration is interpreted as being predominantly controlled by sediment stratigraphy in the early stages of the experiment. However, either the increasing flow rate, or the total injected volume become the dominant factors determining CO2 migration later in the experiment.